Susan Torntore and students documenting textiles - Unidentified photographer (Colorado State University. Libraries, 2015)
Photograph of students assisting Curator Susan Torntore with documentation of a new donation of textiles to the collection in 2015. Students are working over garments on tables, and Torntore is looking at a spreadsheet.
Keywords: Fashion -- History; Fashion -- Exhibitions